The rock cycle - Nelson, Maria (New York, NY : Gareth Stevens Pub., 2014)
Provides an introduction to the rock cycle.
Includes bibliographical references (p. 23) and index.
5.5
3-6
Keywords: Rocks -- Juvenile literature; Fossils -- Juvenile literature; Rocks; Fossils; Rocks; Fossils